Novel approaches on root canal disinfection methods against E. faecalis - Binhong Wu; Zhinuo Zhou; Xingwen Hong; Ziman Xu; Yuou Xu; Yushan He; Shu Chen (Journal of Oral Microbiology)
Background Enterococcus faecalis (E. faecalis), the main pathogenic bacterium of root canal infection, can penetrate deep into the dentin tubule, form a biofilm, and resist host defense mechanisms, thereby increasing treatment complexity. Therefore, the key to the treatment of root canal infections is to completely kill the bacteria and prevent secondary infection. This review assesses advancements in traditional and novel disinfection methods targeting E. faecalis biofilm.Methods By comparing the bactericidal mechanisms and effects of the individual and combined application of these methods, the scientific basis and clinical application potential of these methods as adjuvant or alternative treatments were evaluated and the scientific basis for the optimization of the root canal treatment strategy was provided.Results Emerging strategies, including natural medicine, antibacterial photodynamic therapy, and cold atmospheric plasma, have shown promising antibacterial effects.Conclusion These approaches have the potential to replace traditional disinfection methods, offering more effective solutions for clinical pulp treatment.